Parents-to-be with Overly Optimistic Expectations of Parenthood: Who Are They and What Should Counsellors Do? - Bouchard, Geneviève (Canadian Journal of Counselling and Psychotherapy, 2009)
A fair number of parents-to-be expect parenthood to be the impetus for improving their couple relationship, but this expectation is likely to be disconfirmed for most of them. With a focus on childrearing attitudes, the author investigates the factors differentiating parents-to-be who have overly optimistic expectations about parenthood from those who have realistic expectations. A sample of 174 French-Canadian couples expecting their first child completed questionnaires during the last trimester of pregnancy. Results indicated that, compared to realistic parents-to-be, those with overly optimistic expectations show less complexity in their attitudes toward childrearing. Implications of these findings for counsellors are discussed.